Care management of the multidisciplinary team who acts as Reference Technicians in Psychosocial Care Centers – CAPS (Research, Society and Development, 2022)
Objective: to evaluate the care management of multidisciplinary team who act as Reference Technicians in CAPS.  Methodology: This is a quali-quantitative study whose data were collected from November 2021 to May 2022, through the application of an online questionnaire, which had the participation of professionals from multidisciplinary team who act as Reference Technicians (TR) in Psychosocial Care Centers – CAPS from the Pará state network in Belém. The study populations consisted of higher education professionals, such as nurses, psychologists, psychiatrics, social workers, occupational therapists and administrator, who agreed to participate in the research by signing the Free and Informed Consent Term – TCLE. The data was analyzed using the Iramuteq Platform. Results: Twenty-six professionals participated in the survey, 99% of which were female, with ages ranging from 34 to 58 years. It was observed regarding the attendance of the main activities developed by the TR, that in the CAPS individual, group and Family guidance are available, in addition to review and monitoring welcomed and accompanied users through individual or group psychotherapy with the inclusion of therapeutic workshops, visits households, with emphasis on the technical team’s meetings. In this way, it is concluded that the health professionals who work in the care in CAPS users, among them the reference technicians, develop a series of activities with the users, alleviating the symptoms with a focus on social reintegration.